Pemanfaatan XML Digital Signature Studi Kasus Integritas Transkrip Nilai Online Berbasis XML - Bernard Renaldy Suteja; Ahmad Ashari (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2007)
As the internet technology’s growth, many universities have developed online access integratedacademic system (IAS). Viewing student’s transcript online is one of many important IAS’ outputs. In fact, thatcapability can not eliminate paper based transcript, because it’s based on HTML which is downloadable,modifiable and unstandard layout. The solution for the last problem is XML document format, since it is easierto use especially for data interchange. Meanwhile, for the first two problems which can cause securityproblems, Crypthography can not ensure that the information is authentically and originally created by anauthorized user. Thus, XML Digital Signature is proposed.Keywords: XML, XML Digital Signature, XML Security, XML Secure